Precipitacija v vodi netopnih bakrovih soli v lesu kot zaščita pred glivami razkrojevalkami lesa - Levanič, Jaka (Acta silvae et ligni, 2025)
This study presents a method for protecting wood against fungal decay by precipitating insoluble copper salts within the lumina of wood cells using a two-step impregnation process. The procedure involves treatment with soluble copper sulfate followed by fixation with sodium carbonate. Fixation with sodium carbonate proved to be an effective method for reducing copper leaching from treated specimens. The natural retention capacity of copper in pine sapwood was around 2000 ppm, as determined by the leaching test according to SIST EN 84. With fixation, we successfully retained on average more than 5000 ppm of copper in the samples and almost completely prevented copper leaching from specimens impregnated with a 0.5% copper sulfate solution (0.5% corresponding to the concentration of copper ions in the solution). Despite sufficient copper concentration, the precipitated form of basic copper carbonate in the wood did not act as an effective fungicide, most likely due to its very low solubility in water (< 0.005 g/L at room temperature). Mass loss results according to SIST EN 113-1 indicated poor protection against Coniophora puteana and satisfactory protection against Gloeophyllum trabeum.
Keywords: bakrovi biocidi; copper biocides; copper fixation; fiksacija bakra; fungal decay; glivni razkroj; wood protection; zaščita lesa